Résister aux normes de l’espace public. Les lieux des minorités sexuelles et de genre à Beyrouth - Jean Makhlouta (Genre, Sexualité et Société)
Despite encountering significant social and legal constraints in the Near East, sexual and gender minorities develop strategies to assert their right to the city. Through an ethnographic study combining semi-structured interviews and participant observations, this article aims to understand how these minority groups negotiate a place in the city of Beirut. Focusing on two café bars frequented almost daily by participants, the analysis reveals practices that resist dominant norms which otherwise limit their access to the city’s public space. These acts of resistance manifest both within and outside these commercial establishments, demonstrating diverse spatial and temporal strategies that vary according to the urban and political context in which they occur. Space, as both a social and material construct, emerges as a resource for ensuring access to the city which nonetheless remains unequal due to gender, socioeconomic, and religious-related criteria.